1997
DOI: 10.1159/000244484
|View full text |Cite
|
Sign up to set email alerts
|

Distribution between Protein-Bound and Free Forms of Plasma Cortisol in the Gilt and Fetal Pig Near Term

Abstract: Thirty-five time-dated pregnant gilts were used to document plasma levels of total and free cortisol, corticosteroid-binding globulin (CBG) binding capacity, and percent distribution of cortisol among protein-bound (CBG and albumin) and free forms in the fetal pig during the last 24 days of gestation. Plasma from fetal pigs on days 110–114 of gestation (gestation length 114 days) had significantly higher levels of total cortisol (p < 0.01), percent albumin-bound and free cortisol (p < 0.10), and free cortisol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 26 publications
0
6
0
1
Order By: Relevance
“…Indeed, plasmatic concentrations of CBG do not vary around parturition [4], while cortisol concentrations show a 4-fold increase during farrowing. The binding capacity of CBG for cortisol is therefore likely exceeded [69] and the free cortisol fraction increases up to 28% of the whole fraction around parturition instead of 10-13% during gestation [69,70].…”
Section: Comparison Of Hormone Concentrations In Plasma and Other Fluidsmentioning
confidence: 99%
“…Indeed, plasmatic concentrations of CBG do not vary around parturition [4], while cortisol concentrations show a 4-fold increase during farrowing. The binding capacity of CBG for cortisol is therefore likely exceeded [69] and the free cortisol fraction increases up to 28% of the whole fraction around parturition instead of 10-13% during gestation [69,70].…”
Section: Comparison Of Hormone Concentrations In Plasma and Other Fluidsmentioning
confidence: 99%
“…A previous study in pigs also indicated an increase of maternal and fetal plasma cortisol until parturition [35], [36]. However, the LP diet caused higher salivary cortisol concentrations compared to AP and HP sows; this result reflects a higher concentration of unbound biologically active cortisol in LP sows.…”
Section: Discussionmentioning
confidence: 75%
“…In the Asian elephant, the mechanisms for these changes in circulating maternal hormones is still under study, though Meyer et al (2004) suggest they may be similar to other mammalian species. Fetal cortisol has been shown to start a cascade of events that initiates parturition in other mammalian species, including sheep (Rees et al 1975, Challis et al 2000, pigs (Kattesh et al 1997), and the wallaby (Ingram et al 1999). In other mammalian species, activation of the fetal hypothalamic-pituitary-adrenal (HPA) axis and increased fetal cortisol may induce two primary outcomes via normal endocrine actions: conversion of maternal progesterone to estradiol, and driving maternal hormones to regress the corpus luteum (Senger 2003).…”
Section: Discussionmentioning
confidence: 99%